Brothers in arms: An experiment on the alliance puzzle - Changxia Ke; Kai A. Konrad; Florian Morath (Center for Economic Studies and ifo Institute (CESifo), 2010)
Our experimental analysis of alliances in conflicts leads to three main findings. First, even in the absence of repeated interaction, direct contact or communication, free-riding among alliance members is far less pronounced than what would be expected from non-cooperative theory. Second, this possible solidarity among 'brothers in arms' when fighting against an outside enemy may rapidly deteriorate or disappear as soon as the outside enemy disappears. Third, when fighting an outside enemy, 'brothers in arms' may already anticipate future internal conflict about dividing the spoils of winning; however, this subsequent internal conflict does not discourage alliance members from expending much effort in the contest against the external enemy.
Keywords: D72; D74; 330; alliance; conflict; contest; free-riding; hold-up problem; solidarity; Politischer Konflikt; Internationale Zusammenarbeit; Trittbrettfahrerverhalten; Solidarität; Public Choice; Theorie